Implementation of four‐leg distribution static compensator. Issue 6 (1st June 2014) - Singh, Bhim; Arya, Sabha Raj; Jain, Chinmay; Goel, Sagar
Abstract : An implementation of a four‐leg distribution static compensator (DSTATCOM) using an adaptive neural network‐based control algorithm for compensation of linear/non‐linear loads using voltage source converter is presented here. The proposed control algorithm, which is based on adaptive neural network, is used for extraction of fundamental active and reactive power components of load currents which are major components in the estimation of reference supply currents. This control algorithm is implemented on a developed four‐leg DSTATCOM for reactive power compensation, harmonics elimination, load balancing and neutral current mitigation under linear and non‐linear loads. The performance of DSTATCOM is observed quite satisfactory under various linear and non‐linear loads.